Optimizing the Role of the Language Court in Developing Students' Arabic Speaking Skills: A Case Study at MTsS Nurul Falah Meulaboh - Syarifuddin Hasyim; Tarmizi Ninoersy; Fadhilah; Nuzul Wahyudi (Barkah Publishing, 2025)
This study examines the role of the Language Court in improving students' Arabic speaking skills at MTsS Nurul Falah Meulaboh. Using a qualitative descriptive case study approach, data were collected through interviews and document analysis to explore the pedagogical benefits and potential drawbacks of this institutional practice. The results indicate that the Language Court has three main functions: organizing individual and group language activities, implementing gradual sanctions for violations of language usage rules, and enriching the language environment through structured programs. This system has been shown to foster discipline and provide consistent speaking practice opportunities, but certain forms of punishment, particularly physical or psychological ones, have the potential to negatively impact student well-being. This study recommends a balanced approach between discipline and motivational support to ensure the goal of improving speaking skills is achieved without neglecting student well-being